PENGARUH PENAMBAHAN TEPUNG TAPIOKA YANG BERBEDA TERHADAP NASI RASKIN HASIL UJI SIFAT KIMIA DAN ORGANOLEPTIK - Abdurrahman, Abdurrahman; kadir, Syahraeni; Hutomo, Gatot Siswo (AGROTEKBIS, 2018)
Tapioca flour is one of the products processed by cassava which is widely used as the main raw material and auxiliary material in several food products both in the household and industry. The purpose of this study was to determine the effect of the adding of different tapioca flour, which gives a fluffy taste to raskin rice through testing of chemical and organoleptic. The research method used two types, namely completely randomized design (RAL) and randomized block design (RAK) with five treatments and each treatment repeated 3 (three) times so that there are 15 units of experiment every treatment contained 200 g of raskin rice, if five treatments meant that rice would be used as much as 1 kg. the treatment that will be used is P0 = (without treatment) 200 g of raskin rice and tapioca flour as per the concentration given to P1 0.4g, P2 0.8g, P3 1.2g and P4 1.6g. Chemical properties test results with the addition of tapioca flour in the water content test with the addition of 1.6, ash content with the addition of 0.4 and digestibility with the addition of 1.2 gives effect to the acceptance of raskin rice and organoleptic test of color, aroma, taste, texture and preference with the addition of tapioca flour 1.6 give a very significance on the acceptance of raskin rice.